Short distance migrants travel as far as long distance migrants in lesser black‐backed gulls Larus fuscus. (10th February 2017) - Shamoun‐Baranes, Judy; Burant, Joseph B.; van Loon, E. Emiel; Bouten, Willem; Camphuysen, C. J.
Abstract : Migration strategies differ greatly among and within avian populations. The associated trade‐offs and fitness consequences of diverse strategies and how they persist are pertinent questions in migration research. Migration is a costly endeavour, presumably compensated for by better survival conditions in the non‐breeding area. One way to assess the cost of alternative strategies is to investigate the investment in movement across the entire annual cycle, an assessment made increasingly feasible with improvements in tracking technology. Our study focuses on lesser black‐backed gulls, generalist seabirds that exploit a broad range of resources, exhibit diverse migration strategies and have potentially altered migration strategies in response to human activities and climate change. We used GPS tracking to quantify lesser black‐backed gulls' movement throughout their annual cycle and compare trade‐offs among four migration strategies. The annual cumulative distance travelled by long distance migrants wintering in west Africa, over 4000 km from their breeding colony, did not differ significantly from individuals of the same breeding colony wintering only a few hundred kilometres away in Great Britain. Short distance migrants returned to the colony first, and long distance migrants returned last. Sex and wing length were not correlated with maximum range, cumulative distance travelled or timing. Individuals spent only a small proportion of their time in flight and spent on average 17% of their time at sea throughout an annual cycle, suggesting a reliance on inland resources for many individuals. Analysing movement throughout the annual cycle can change our perspective and understanding of consequences of different migration strategies. Our study shows that a range of migration strategies coexists and we propose that the long term costs and benefits of these strategies balance out. Diversity in migration strategies may contribute to the resilience of this species in the face of ongoing anthropogenic impact on the environment.